Design of Informatic Logic Teaching Meterial Appication Using Ideal Problem Solving Based on Android Case Study in Universitas Pamulang - Tita Puspitasari (Data Science: Journal of Computing and Applied Informatics, 2022)
Basic Physics is a part of physics that studies about objects in nature, the symptoms of natural events and the interactions of objects in nature. This symptom is initially what our senses experience. For example, sight finds optics or light, hearing finds learning about sound, heat can also be felt (felt). In defining a quantity in physics, there must be rules for calculating the quantity in question based on other measurable quantities. In Basic Physics, it is necessary to understand the flow of questions well to how to calculate and explain them. However, sometimes students do not understand this course due to weakness in calculations or lack of understanding of material concepts and the use of formulas. For this reason, it is necessary to have the latest learning methods through Android to improve student understanding. The purpose of this paper is to determine whether the use of the IDEAL problem solving model based on Android is effective, because based on several researches, iDEAL problem solving can improve students' process skills, increase motivation and improve problem solving abilities. The results of this research are in the form of an application that is used as one of the innovative and android-based learning media so that it is more practical to learn anywhere and anytime.